Consumption growth, the interest rate, and financial sophistication*. (18th July 2016) - JAPPELLI, TULLIO; PADULA, MARIO
Abstract: We propose a model in which financial sophistication improves portfolio returns and therefore the incentive to substitute consumption intertemporally. The model delivers an Euler equation in which consumption growth is positively correlated with financial sophistication. We test the model's prediction using panel data on consumption and financial sophistication drawn from the Italian Survey of Household Income and Wealth. We find that consumption growth is positively correlated with financial sophistication, as predicted by the model. We also provide estimates of the intertemporal elasticity of substitution in the range between 0.4 and 0.6.